Dampak Implementasi Dana Pemberdayaan Ekonomi Masyarakat Terhadap Peningkatan Pendapatan Masyarakat - Frits O Fanggidae; Ronald Patrick Costantin Fanggidae (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2016)
Impact of PEM funds towards increasing income of the beneficiaries are signivifant, although the majority of revenue still used for consumption (51.31%) and the remainder is used to increase business capital (48.69%) . In terms of the principles of empowerment , with the additional capital through the income, recipients PEM start empowering their business well. However , the choice of the type of business has not varied (focus on trading activities), inadequate of business planning and financial managament. Because it is recommended that improvements in the implementation of PEM funds focus on expanding business options, and improvements in the planning and financial managament as well as.